2012
DOI: 10.3856/vol40-issue2-fulltext-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluacion del potencial reproductivo del chorito (Mytilus chilensis) de dos poblaciones naturales sometidas a diferentes temperaturas de acondicionamiento

Abstract: RESUMEN.Mytilus chilensis tiene ciclos reproductivos que varían latitudinalmente. Presenta reducida diferenciación genética y morfológica debido a un gran potencial de dispersión. Se acondicionaron reproductores de bahía Yaldad (Chiloé) y bahía Zenteno (Punta Arenas) a 9 ± 0,5°C y 15 ± 0,5ºC, alimentados con dieta (1:1) de Isochrysis galbana y Chaetoceros neogracile. Se espera dilucidar si el acondicionamiento a diferentes temperaturas produce variaciones en el potencial reproductivo de las poblaciones. El men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Our results demonstrated that oocyte size in both p CO 2 levels were smaller (∼2 μm) than reported by Lagos et al (2012b) for M. chilensis but within the range reported by Ockelmann (1965) for a number of bivalves. No effect in oocyte size from broodstock exposed to high p CO 2 levels was observed.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results demonstrated that oocyte size in both p CO 2 levels were smaller (∼2 μm) than reported by Lagos et al (2012b) for M. chilensis but within the range reported by Ockelmann (1965) for a number of bivalves. No effect in oocyte size from broodstock exposed to high p CO 2 levels was observed.…”
Section: Discussionsupporting
confidence: 87%
“…Our experimental approach considered an initial spawning of adult mussels in order to homogenize the state of gonadal development prior to reproductive conditioning under two OA scenarios (550–1200 p CO 2 ) and otherwise optimal conditions of food supply and temperature. While previous experimental studies in M. chilensis have reported conditioning periods of up to 81 days at 15°C ( Lagos et al, 2012b ), we extended this period to ca. 4 months to be consistent with other transgenerational OA experiments in mollusks ( Parker et al, 2012 , 2017a ; Fitzer et al, 2014 ; Griffith and Gobler, 2017 ; Zhao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for adult individuals the exposure time was shorter, since adult mussels considered in our study were at pre-spawning stage (50 mm shell length, Lagos et al . 58 ). It is well known that after that size, adult mussels change their energy expenditure destined mainly to the reproduction phase 59 .…”
Section: Methodsmentioning
confidence: 99%